Automated precision pulse capsulotomy vs manual capsulorhexis in white cataracts: reduction in procedural time and resource utilization. Issue 4 (6th April 2023) - Ifantides, Cristos; Sretavan, David
Abstract : Precision pulse capsulotomy (PPC) was compared with continuous curvilinear capsulorhexis in white cataracts in a single-surgeon retrospective study. PPC showed advantages in capsulotomy metrics, resource utilization, and surgical flow. Abstract : Purpose: To compare the utility of precision pulse capsulotomy (PPC) with manual capsulorhexis for capsulotomy in white cataracts. Setting: Hospital-based academic practice. Design: Retrospective analysis of surgical case records and surgical videos from a single surgeon. Methods: Cases involving intumescent and nonintumescent white cataracts were identified. Capsulotomy outcomes, surgical outcomes, procedural time, and resource utilization, as well as patient demographic and health data, were analyzed and subjected to statistical testing. Results: 15 cases of white cataract (10 intumescent and 5 nonintumescent) performed using continuous curvilinear capsulorhexis (CCC) were compared with 20 cases (9 intumescent and 11 nonintumescent) performed using PPC. The cases covered a period of 14 months before and 30 months after surgeon adoption of PPC. There were no significant differences between the 2 groups in patient age, sex, ethnicity, ocular history, medical history, and medications. PPC resulted in complete capsulotomies without tags or tears and intracapsular intraocular lens implantation with 360-degree capsular overlap in all 20 cases. There was 1 CCC case resulting in the Argentinian flag sign. Compared with CCC, PPC white cataract cases also demonstrated significant advantages in capsulotomy time, reduced use of trypan blue and ophthalmic viscosurgical device, and less overall procedural time. Conclusions: PPC is a safe and highly effective method to create consistent capsulotomies in both intumescent and nonintumescent white cataracts. The use of PPC provides benefits of significant reductions in capsulotomy time, overall procedural time, and resource utilization, resulting in a streamlined treatment of these complex cataract surgery cases.